(untitled) (Orinoquia, 2021)
The 3rd International Congress of Basic Sciences and Engineering (Congreso Internacional de Ciencias Básicas e Ingenierías – CICI) 2020 was held between August 11th and 13th; it was organised by the Universidad de Los Llanos’ Faculty of Basic Sciences and Engineering. The hardships caused by the COVID-19 pandemic regarding the public health emergency meant that the congress was held virtually for the first time during these 3 days. It was open to the general public, academics, students, professors/teachers, researchers, professionals from seedbeds and national and international research groups to promote the exchange of academic and research experience regarding basic sciences, engineering and related areas Eleven speakers were invited to address the congress from Colombia, México, Guatemala, the USA and Chile; four workshops were held, there were four panellists and 240 people registered on the Geducar-Unillanos platform. Ninety-six people enrolled for the event and more than 150 people attended daily during the three-day event; they accessed it through the YouTube videoconference streaming platform. The state of the art and the methods, techniques and applications used in different thematic areas were updated, including COVID-19-related dynamics, thereby contributing towards consolidating knowledge networks. A panel entitled, “The role of Basic Sciences and Engineering in the region: experiences, reflexions, challenges and perspectives regarding COVID-19,” was held with people invited from the health, basic sciences and engineering, bioethics and philosophy sectors as a space for analysis and reflexion concerning the current situation, changes, future perspectives and our role regarding new post-pandemic reality. Authors from 8 countries (Argentina, Benin, Colombia, Cuba, Greece, Mexico, Pakistan, Spain) submitted 132 papers for participating in CICI 2020; these were peer-reviewed and evaluated by the scientific committee (58% acceptance rate). Papers were accepted from 200 authors from 42 national and international institutions, including the Universidad de los Llanos. The event finally featured 71 papers given as oral presentations in the following areas: Electronic Engineering, Systems and Related Areas; Mathematics, Physics and Statistics; the Environment: Biology, Chemistry and Environmental Management; COVID-19 prevention, mitigation, diagnosis and effects. All of these are available in the reports published on the CICI 2020 event page “Advances in Basic Sciences and Engineering in times of COVID-19”: http://cici.unillanos.edu.co/ es/2020/autores/memorias/ ISSN: 2744-9599 (Online). The authors of some papers published in the proceedings of the event having the highest peer-review evaluations by the experts were invited to send extended versions of their work to be peer-reviewed again to be edited in this special issue. We would therefore like to thank the reviewers and authors for their interest and efforts at maintaining the standards of quality required by Orinoquia. CICI 2020 thus enabled participants to become familiar with work from areas in common from other perspectives and those attending the event to become acquainted with what is being done at the Universidad de Los Llanos, institutions from the region, Colombia and other countries. It also led to the integral and interdisciplinary strengthening of scientific and professional training, the formation of academic networks and contacts for academic and scientific cooperation with civil society to promote the development of inter-institutional cooperation projects, scientific dissemination and the social appropriation of knowledge, having an impact on the region and Colombia for the academic and productive sector’s sustainable development which is fundamental in such post-pandemic times. Without further ado, we would like to thank the people and institutions that supported us and participated in such a successful academic and scientific meeting, wishing readers an enriching and profitable appraisal of the works included in this supplement.